A 3D‐printed modular reactor setup including temperature and pH control for the compartmentalized implementation of enzyme cascades. Issue 6 (23rd August 2016) - Kazenwadel, Franziska; Biegert, Ellen; Wohlgemuth, Jonas; Wagner, Henrike; Franzreb, Matthias
Abstract : In recent years, 3D printers developed rapidly from an expensive niche product used mainly by architects and designers into a versatile tool for engineers helping them to quickly realize and test new ideas. While most of the reported examples still focus on the use of 3D‐printed parts as mechanical but chemically inert tools, we developed a 3D‐printed modular reactor system which allows the fast implementation and testing of enzyme cascades. 3D printing offers several advantages in this context, as complex fluidic structures that cannot be fabricated by other methods can be generated, and the printed reactors are easily scalable in order to adjust their size to specific reaction parameters. Using a so‐called PolyJet technique, highly porous monolithic enzyme carriers were printed and directly UV‐cured from acrylate monomers, allowing simple immobilization of enzymes in a subsequent step. The enzyme immobilisates were fixed in a 3D‐printed housing with integrated fluid distributors forming a compact module to conduct a biotransformation step. Several of such modules can be connected in series to a pumping and analyzing system. A model cascade connecting two enzyme transformation modules, the first containing Glucose Oxidase and the second containing Horseradish Peroxidase, was operated using a commercial FPLC system for flow control and UV–Vis detection of the generated product. In order to adjust the temperature, a Peltier‐based tempering jacket for the enzyme transformation modules was designed. In addition, a flow‐through pH regulation module was developed, based on an electrochemical principle which allows unidirectional pH changes without the need for membranes or discharge of partial fluid streams. Except for the electrodes, also the pH regulation module was fabricated by 3D printing.